Self-Testing as an Invaluable Tool in Fighting the COVID-19 Pandemic. (September 2021) - Goggolidou, Paraskevi; Hodges-Mameletzis, Ioannis; Purewal, Satvinder; Karakoula, Aikaterini; Warr, Tracy
Objectives: The United Kingdom and a number of European Union countries are offering and distributing rapid antigen detection tests (RADTs) for self-test use to detect SARS-CoV-2. For instance, Greece, in the midst of its third wave of COVID-19, announced the provision of RADTs for self-testing through retail pharmacies. With the aim to determine the acceptability and feasibility of COVID-19 self-testing, we ran a cross-sectional survey on residents of Greece and Cyprus, aged over 18 years. Methods: An online survey using the JISC platform was distributed to 1000 individuals who completed the survey anonymously. Data was collated and analyzed for complete responses by chi-squared and logistic regression analyses. Results: A total of 248 complete responses were obtained, with balanced gender distribution and particular demographics representative of the 2 countries. The majority of participants (79%; n = 196) reported willingness to self-test and the remaining individuals reported no (10.5%; n = 26) or don't know (10.5%; n = 26). Being a university graduate significantly predicted the likelihood of being willing to self-test (odds ratio [OR] = 3.455, P < .001). Pearson Chi-square test found significant differences between university graduates versus non-graduates on the type of COVID-19 test preferred (χ 2 = 8.95, df = 3, P < .03); graduates were more likely to prefer saliva testing and less likely to prefer the finger prick test than non-graduates. Conclusions: Our survey data evidences the acceptability of home-based self-testing, with a preference for saliva as choice of biological material for sampling. A number of factors, such as accessible reporting, contact tracing infrastructures, central registration, and validation for the implementation of different RADTs need to be taken collectively into consideration before self-testing can be universally and reliably scaled up.